PAI Teacher's Creativity Strategy in Utilizing Learning Media Based on Independent Curriculum - Putri, Adzqi Amalia; Hasanah, Uswatun; Asiah, Nur; Hijriyah, Umi; Jalaluddin, Jalaluddin (STAI Syaichona Moh. Cholil Bangkalan, 2025)
Implementing the independent curriculum requires teachers to actively design innovative and creative learning actively, especially in using learning media. Along with the development of increasingly sophisticated technology, teachers are required to use media by the times. However, the limited knowledge of teachers and the availability of media facilities are still obstacles to teachers' implementation. This study examines PAI teachers' creativity strategies in utilizing media based on the independent curriculum in class VII at SMP IT Al-Banna Natar. Using descriptive qualitative research with data collection techniques through interviews, observation, and documentation. The results showed that PAI teachers had fulfilled the indicators of creativity in the selection of learning media. Despite the limited facilities at school, PAI teachers implemented several strategies: 1) utilizing the surrounding environment as a learning medium. 2) Improving knowledge and skills 3) Building collaboration with other teachers. The renewal of this research is the application of PAI teachers' strategies to increase creativity by utilizing the surrounding media, which has rarely been studied in previous studies. The implication of this research is expected to enrich the understanding of teacher creativity strategies in utilizing learning media.